Recherche pax romana désespérément - Christophe Badel (Kentron, 2024)
During the Roman Republic, peace was not a state but a moment, the signing of a treaty with a defeated enemy, and Rome was still at war at that time. Following the civil wars, Augustus made peace an ideal of government but the official documents (coins and inscriptions) valued the peacemaking role of the emperor especially from the Flavians and even more from the Severans. It is not easy to distinguish peace from victory because their benefits are similar, security and prosperity. Called Pax Augusta by official documents, peace appears as the work of the emperor and the Pax Aeterna formula refers to the imperial Aeternitas. The term Pax Romana is rather rare and generally refers to the peace imposed by Rome on its enemies and takes on a broader meaning only in Seneca, Pliny the Elder and Martial. It then refers to the Imperium Romanum and not to a specific political concept, as modern historians believe. The Romans knew only one peace: the Pax Augusta.